The Role of Gender in Evaluation of Start-Up Pitches: A Literature Review - Mateusz CODOGNI (Communications of International Proceedings, 2025)
Attracting early-stage investors is a vitally important part of developing a start-up. An early stage of this process, that can be described as a screening mechanism, is pitching. While the assessment of the business prospects based on pitches is partly involves analysing their factual content, it is also largely susceptible to snap judgements based on ‘gut feelings’. For this reason, it is important to investigate these largely non-rational factors that influence early investment decisions. One such factor is gender of the entrepreneur. This paper is a scoping literature review. As the gender gap in early-stage investment is a broad and complex topic, this paper aims to map its component areas. It also aims to determine which of the areas wave been well researched and a where a consensus has emerged, and which areas have been under-researched and where the outcomes are unclear. The literature review points to conclusion that the gender gap does exist, and is partly based on gender stereotypes and biases. It also appears to be, at least partly, rooted in the homophily exhibited by male investors. The contribution of this paper is to consolidate disparate strands of research and to offer an overview, especially on the understudied topics, like specific causes of the differential treatment of men and women in start-up ecosystem.
Keywords: entrepreneurship; startup; venture capital; gender gap; gender bias